The effect of coarse aggregate structure on the performance of porous asphalt mixture - Tan, Qing Yi (2014)
The feasibility of the usage of porous asphalt mixture for light traffic road pavement, principally for pedestrians and bicycle cycling paths, was investigated in this project. The aim is to come up with a design that would be suited to be applied on pavements in Singapore and to evaluate how the performance of porous asphalt mixture (PAM) would vary with the different amount of coarse aggregate content.